Evaluación de protocolos de síntesis de nanopartículas de cobre u óxidos de cobre - Acevedo-León, Daniela; Ossa-Orozco, Claudia Patricia; Torres-López, Ana María (Ingeniería, 2023)
Context: Copper or copper oxide nanoparticles are materials of interest in the field of agriculture due to their multiple properties, including their antimicrobial activity, which is useful in the biological control of pests. Several authors have reported that nanoparticles smaller than 50 nm have a greater antimicrobial effect. Accordingly, this study aimed to compare different synthesis protocols, with the purpose of obtaining copper or copper oxide nanoparticles with adequate size for their subsequent evaluation in the biological control of species that commonly affect crops in Colombia. Method: Five synthesis protocols were evaluated, four of them classified as green chemical synthesis methods, and the other as biological synthesis. The obtained nanoparticles were characterized via UV-Vis spectroscopy, DLS, TEM, FTIR, XRD, SEM, and EDS. Results: Protocol 3, which uses copper sulfate pentahydrate as precursor salt, ascorbic acid as reducing agent, and starch as stabilizer, proved to be the most suitable, as spherical metallic copper nanoparticles with a size of 4,5 nm were obtained with it. Conclusions: It was possible to compare methodologies for copper and copper oxide nanoparticles production, analyze the effect of synthesis conditions on their characteristics, and finally obtain a protocol to synthesize copper nanoparticles with an adequate size for potential use in biological control applications.